Moderate expression of TRF2 in the hematopoietic system increases development of large cell blastic T-cell lymphomas - Begemann, Sebastian (Impact Journals LLC, 2009)
The telomeric repeat binding factor 2 (TRF2) plays a central role in the protection of chromosome ends by inhibiting telomeres from initiating a DNA damage cascade. TRF2 overexpression has been suggested to induce tumor development in the mouse, and TRF2 levels have been found increased in human tumors. Here we tested whether moderate expression of TRF2 in the hematopoietic system leads to cancer development in the mouse. TRF2 and a GFP-TRF2 fusion protein were introduced into hematopoietic precursors, and tested for function. TRF2 overexpressing cells were integrated into the hematopoietic system of C57BL/6J recipient mice, and animals were put on tumor watch. An increase in the development of T-cell lymphomas was observed in secondary recipient animals, however, overexpression of the TRF2 transgene was not detectable anymore in the tumors. The tumors were characterized as large cell blastic T-cell lymphomas and displayed signs of genome instability as evidenced by chromosome fusions. However, the rate of lymphoma development in TRF2-overexpressing animals was low, suggesting the TRF2 does not serve as a dominant oncogene in the system used.